Belt and Road Initiative – Challenges and Opportunities for Europe - Sharma, Piyush; Leung, Tak Yan; Davcik, Nebojsa; Cardinali, Silvio (2020)
China’s Belt & Road Initiative (BRI) is an ambitious global infrastructure development strategy that covers 152 countries around the world. Despite strong support from the Chinese government, public response to BRI has been quite mixed in Europe, because people are still not sure about how this would benefit or harm their individual and national interests. We address this uncertainty about the potential outcomes of BRI by exploring how it is perceived by the managers working in professional services firms in the partner countries in Europe. We also introduce a new construct, ‘BRI-Readiness’, the ability of managers and organizations to face the challenges and tap the opportunities offered by BRI. We also plan to develop a scale to operationalize BRI-Readiness. Finally, we explore the impact of psychic distance (in terms of their cultural values and business practices) and cultural familiarity on the acceptance of BRI by the managers in professional services firms in Europe.